Nutritive value and yield potential of okra (Abelmoschus esculentus L. Moench) genotypes (Bangladesh Journal of Agricultural Research, 2016)
Two experiments were conducted at the research field and laboratory of the Department of Horticulture, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Salna, Gazipur, during April 2012 to September 2013 to find out the yield performance and nutritional quality of seven genotypes of okra in Bangladesh. The results revealed that the highest yield of okra obtained from BARI Dherosh1 (14.9 t/ha) and the lowest yield was obtained from Hybrid Raja (5.76 t/ha). The highest fruits per plant were recorded from BARI Dherosh1 (24.27 fruits/plant). The genotype Green Hybrid produced the lowest edible fruit per plant (10.27). Maximum virus infestation was recorded in genotype Hybrid Raja (100%) and the lowest in Arka Anamika (76.67%) as well as Arka Anamika performed well in many aspect such as yield (12.95 t/ha), fruits per plant (19.83), number of branches per plant (6). The highest content of free ascorbic acid was recorded in Nabik (3.35 mg/100gm) and the minimum ascorbic acid content was observed in Green Hybrid (1.987 mg/100g). Hybrid Moti had the maximum amount of ?-carotene (0.15 IU/100 g), while minimum amount of ?-carotene was found in IPSA Okra (0.09IU/100 g). The highest K content was observed in IPSA Okra (1.091%) and the lowest in Hybrid Raja (1.06%). The highest amount of Fe was observed in Hybrid Moti (139.60 ppm) and the lowest amount of Fe was observed in Green Hybrid (111.80 ppm). The present results revealed that the yield was maximum in BARI Dherosh1 while Hybrid Moti was superior in nutritive value.Bangladesh J. Agril. Res. 41(3): 541-554, September 2016